Analisis Pengaruh Variabel Kualitas Layanan Terhadap Kepuasan Pelanggan Apotek Kimia Farma Jember - Choirunnisa' Kurnia Safitri; Ketut Indraningrat; Imam Suroso (e-Journal Ekonomi Bisnis dan Akuntansi, 2017)
This research aimed to analyze the effect of variable quality services to customer satisfaction in Kimia Farma PharmacyJember. The population in this research are customers of Kimia Farma Pharmacy Jember. Sampling method used is purposivesampling with the number of respondents 108 people. Variables used are 5 variables. This research located in Kimia FarmaPharmacy Jember. Primary data used in this research is the answer of the questionnaire, while secondary data in this study is ageneral overview of Kimia Farma, literature from many sources, and also from previous research. The analysis tool usedAnalysis Structural Equestion Modelling (SEM). The results showed that: 1) Physical evidence significantly effect oncustomer satisfaction in Kimia Farma Pharmacy Jember; 2) Reliability significantly effect on customer satisfaction in KimiaFarma Pharmacy Jember, and; 3) Responsiveness significantly effect on customer satisfaction in Kimia Farma PharmacyJember; 4) Assurance a significantly effect on customer satisfaction in Kimia Farma Pharmaciy Jember; 5) Empathysignificantly effect on customer satisfaction in Kimia Farma Pharmacy Jember.